PHYTOCHEMICAL ANALYSIS AND CONSTITUENTS OF HEXANE EXTRACT OF MELASTOMA MALABATHRICUM L - Giri, Dil Prakash; Rajbhandari, Meena (Journal of Institute of Science and Technology, 2018)
Hexane, dichloromethane, ethyl acetate, methanol and 50 % aqueous methanol extracts of leaf, flower and fruit of Melastoma malabathricum were screened for the presence of different classes of phytochemicals. In phytochemical screening, ethyl acetate, methanol and 50 % aqueous methanol extracts showed the presence of phenolics and flavonoids. Glycosides were found only in the 50 % methanol extract of fruit. Free radical scavenging activity of methanol extract of leaf, flower and fruit was determined using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical. Total phenolic content was measured spectrophotometrically using Folin-Ciocalteu, total flavonoids content by using aluminum chloride and total sugar content by using anthrone reagent. Gallic acid was used as a standard for the calibration of phenolics, catechin for flavonoids and glucose for carbohydrates. The highest amount of phenolic was found in the 50 % methanol extract of leaf (242.88 ± 3.52 mg GAE/g extract), the highest amount of flavonoids was found in the ethyl acetate extract of leaf (127.41 ± 6.33 mg CE/g extract). Total sugar in 50 % methanol extract of fruit was found to be 151.12 ± 8.79 mg GE/g extract. Methanol extracts of flower showed the strongest antioxidant activity with IC50 value of 17.23 μg/ml. Silyl derivative of hexane extracts were prepared by using N-methyl-N-(trimetylsilyl) trifluoroacetamide for gas chromatography-mass spectroscopic (GC-MS) analysis. The GC-MS analysis of hexane extract allowed the identification of 17 phyto-constituents by comparing the fragmentation pattern of each component in mass spectrum with the standard NIST mass spectral database.